Higher Education of Students with Disabilities: a Literature Review (Annual of the Faculty of Philosophy in Skopje, 2018)
The proportion of higher education students with disabilities is increasing at universitylevel. In Macedonia, there are no statistics about the number of students with disabilitiesincluded in the academic institutions. The inadequate accessibility of higher educationinstitutions, the lack of support, the negative social attitudes and social isolation, aswell as the low financial capacity influence the success of students with disabilities andaffect their inclusion in the higher education. Тhis study aims to conduct an in-depth reviewof some of these challenges that are present in the higher education of students with disabilities.A detailed analysis of 11 publications was performed. We can conclude from thosepublications that faculty members demonstrate generally positive attitudes towards studentswith disabilities, with some research indicating less favourable attitudes towardsthose with “nonvisible” disabilities, such as learning disabilities. Also, there are conflictingresults as to whether students with disabilities have an equivalent academic performancewith those without disabilities.
Keywords: HIGHER EDUCATION; STUDENTS WITH DISABILITIES; STUDENTS WITHOUT DISABILITIES; ATTITUDES; ACADEMIC ACHIEVEMENT